Automation technology and industrial renewal : adjustment dynamics in the U.S. metalworking sector - Hicks, Donald A. (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1986)
This volume examines patterns of technological change and upgrading in one of the oldest industry complexes in the United States.
Includes bibliographical references: p. 153-160.
ucj 17/01/2019
Loans
Keywords: Metalworking industries